The challenges of blockchain in digital era - Othman, Malisa (Asian Scholars Network, 2023)
The adoption of blockchain technology presents a number of challenges that are causing its widespread adoption. This in-depth investigation looks into blockchain adoption's major challenges, such as stakeholders' lack of awareness and understanding. The study emphasizes the importance of addressing this issue through education and training initiatives to improve knowledge and understanding of blockchain technology. Furthermore, conflicts between organizations emerge as a significant impediment, as divergent interests and competing agendas limit collaboration and consensus-building. Again, the existing business culture frequently resists change, making integrating blockchain solutions difficult. Overcoming this challenge necessitates organizational restructuring and the creation of a culture that values innovation and technological transformation. Furthermore, the high cost and investment required to implement blockchain infrastructure and protocols stymies adoption, necessitating careful cost-benefit analysis and strategic planning. The absence of clear guidelines and frameworks raises legal compliance and consumer protection concerns, exacerbating the challenges. To address these challenges, industry stakeholders, regulatory bodies, and policymakers must collaborate to create supportive regulatory frameworks and promote best practices for governance. Organizations can unlock the transformative potential of blockchain technology and pave the way for its successful integration into various sectors by recognizing and mitigating these challenges.